2014
DOI: 10.1118/1.4892181
|View full text |Cite
|
Sign up to set email alerts
|

Image‐guided transorbital procedures with endoscopic video augmentation

Abstract: Improvements in both target identification accuracy and interventional procedure time suggest that endoscopic video augmentation provides valuable additional orientation and trajectory information in an image-guided procedure. Utilization of video augmentation in transorbital interventions could further minimize complication risk and enhance surgeon comfort and confidence in the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Unlike in other surgical fields, relatively few studies utilized AR for surgical guidance. 33 , 34 DeLisi et al 33 found that surgeons who used their video augmentation system experienced faster endoscopic procedural times than surgeons who did not use AR ( P = 0.020). Pan et al 34 developed and implemented a deep learning framework to accurately detect corneal contours for accurate suturing in deep anterior lamellar keratoplasty procedures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike in other surgical fields, relatively few studies utilized AR for surgical guidance. 33 , 34 DeLisi et al 33 found that surgeons who used their video augmentation system experienced faster endoscopic procedural times than surgeons who did not use AR ( P = 0.020). Pan et al 34 developed and implemented a deep learning framework to accurately detect corneal contours for accurate suturing in deep anterior lamellar keratoplasty procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike in other surgical fields, relatively few studies utilized AR for surgical guidance 33,34 . DeLisi et al 33 found that surgeons who used their video augmentation system experienced faster endoscopic procedural times than surgeons who did not use AR ( P = 0.020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly there are various other specific approaches which we have assigned to the group of information support IGS, including systems providing intraoperative visualization of cumulative instrument positions corresponding to removed tissue providing the surgeon with information about the surgical process over time (process visualization, PV-IGS) (Hong et al, 2009;Voormolen et al, 2012;Woerdeman et al, 2009a), visualization of uncertainty arising from registration, instrument calibration and tracking (uncertainty visualization, UV-IGS) (Simpson et al, 2014), visualization of distances between the surgical instrument and sensitive anatomical structures that need to be protected during the surgery (distance visualization, DV-IGS) (Cho et al, 2013;Voormolen et al, 2012), auditory or visual alerts if the instrument approaches such a structure (proximity warnings, PW-IGS) (Cho et al, 2013;Dixon et al, 2014a;Voormolen et al, 2012;Willems et al, 2005;Woerdeman et al, 2009b), augmentation of risk structures included directly into the whole endoscopic video image or just on its background (augmented risk structures, ARS-IGS) (Dixon et al, 2012;Li et al, 2016), augmentation of target tissue included directly in the microscopic view (augmented target volume, ATV-IGS) (Woerdeman et al, 2009b), augmented cues for small targets (e.g. crosshair) included in the endoscopic video image (augmented target, AT-IGS) (DeLisi et al, 2014;DeLisi et al, 2015), augmented pathways which represent the best way to bring the instrument to a certain target area or tumor directly included in the endoscopic video image (augmented pathway, AP-IGS) (Caversaccio and Frysinger, 2003;Freysinger et al, 1997), or three-dimensional endoscopic virtual visualizations of anatomical structures (threedimensional virtual image guidance, 3DV-IGS) (Dixon et al, 2016;Dixon et al, 2014a).…”
Section: Igs System Functionalitiesmentioning
confidence: 99%